Amplification of health risk messages in leading Philippine newspapers - Nuñez, Jedess Miladel C.; Gravoso, Rotacio S. (Annals of Tropical Research, 2007)
his study aimed to find out the coverage and amplifica catechuion of health risk messages of leading Philippine newspapers: Philippine Daily Inquirer, The Philippine Star, and Manila Bulletin. Data were gathered through a content analysis of health risk articles published by those newspapers in 2005. Results revealed that the health risk articles published in 2005 by the three newspapers focused on bird flu, dengue fever, food poisoning and meningococcemia. However, the three newspapers did not give prominence to health risk articles. In terms of sources of information, most of the articles quoted experts and government officials but were prompted by public experiences. Most of the articles assigned blame or responsibility to organizations rather than individuals. The lexical content analysis using the Language Inquiry and Word Count (LIWC) showed that negative emotion words, words linked to people’s ratings of anxiety, were present in health risk articles, indicating intensification of the health risk. For bird flu articles, most of the negative words were in the pre-peak and post-peak periods, while for dengue fever, in the peak period. For food poisoning and meningococcemia, most negative emotion words in the articles were published during the post-peak period.